Serum taurine affects lung cancer progression by regulating tumor immune escape mediated by the immune microenvironment - Tu-Liang Liang; Hu-Dan Pan; Pei-Yu Yan; Jia-Ning Mi; Xiao-Cui Liu; Wei-Qian Bao; Li-Rong Lian; Cui-Fen Zhang; Ying Chen; Jing-Rong Wang; Ying Xie; Hua Zhou; et al. (Journal of Advanced Research)
Introduction: Taurine is a naturally occurring sulfonic acid involved in various physiological and pathological processes, such as the regulation of calcium signaling, immune function, inflammatory response, and cellular aging. It has the potential to predict tumor malignant transformation and formation. Our previous work discovered the elevated taurine in lung cancer patients. However, the precise impact and mechanism of elevated serum taurine levels on lung cancer progression and the suitability of taurine or taurine-containing drinks for lung cancer patients remain unclear. Objectives: Our study aimed to systematically investigate the role of taurine in lung cancer, with the ultimate goal of contributing novel strategies for lung cancer treatment. Methods: Lung cancer C57 and nude mice models, RNA sequencing, and stable transfection were applied to explored the effects and mechanisms of taurine on lung cancer. Tissues of 129 non-small cell lung cancer (NSCLC) patients derived from 2014 to 2017 for immunohistochemistry were collected in Taihe Hospital. Results: Low doses of taurine, as well as taurine-infused beverages at equivalent doses, significantly enhanced lung tumor growth. Equally intriguing is that the promoting effect of taurine on lung cancer progression wanes as the dosage increases. The Nuclear factor erythroid 2-like 1 (Nfe2l1 or Nrf1)-reactive oxygen species (ROS)-PD-1 axis may be a potential mechanism for dual role of taurine in lung cancer progression. However, taurine’s impacts on lung cancer progression and the anti-tumor function of Nfe2l1 were mainly determined by the immune competence. Taurine inhitited lung tumor growth probably by inhibiting NF-κB-mediated inflammatory responses in nude mice rather than by affecting Nfe2l1 function. As patients age increased, Nfe2l1 gene and protein gradually returned to the levels observed in healthy individuals, but lost its anti-lung cancer effects. Conclusions: Taurine emerges as a potential biomarker for lung cancer progression, predicting poor prognosis and unsuitability for specific patients. Lung cancer patients, especially young patients, should be conscious of potential effects of taurine-containing drinks. Conversely, taurine or its drinks may be more suitable for older or immune-deficient patients.